THE VALUE CHAIN OF FISH TECHNIQUES OF FLOATING CAGES AND PONDS IN DEUANYA PROVINCE - & et al., AL- FLUJy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The fish sector is considered an important component of the economies of many countries in the world including Arab countries. It is also considered an important component of food security. This work is considered as the first attempt to study value chain for fish in Iraq. The objective of this study is to identify the main problems and constrains facing different links in the value chain of fish, and to analyse revenue, production costs, and to calculate some quantitative indicators like value added. The results showed that average value added of the different links is amount to: 22.2dinars/kg , 2012.7 dinar/kg, 109.3 dinar/kg, 872.3 dinars/kg from each links hatcheries, producers, wholesalers and retailers. The results also showed that the share of different links from value chain for average total value additionrs as follows: 0.73% for hatcheries link, 66.7% for producer link , 3.6% for wholesalers link, and 28.9% for retailers link. While cages producers added 65.5% from average value added it is amount to 2912. 7 dinar/ kg; on the level techniques cages floating. The study also identifis the main challenges and problems facing each link in chain value and forward the suitable solution and recommendation for government authorities and private sector in order to increase the efficiency of fish in Iraq.